Bentuk Implikatur Percakapan dalam Transaksi Jual Beli di Pasar Sumani Kecamatan X Koto Singkarak Kabupaten Solok - Halid, Elan; Erlina, Erlina (IdeBahasa, 2023)
Pragmatics is the study of language usage in relation to its context. In buying and selling interactions, sellers and buyers use spoken language to facilitate the transaction process. Regarding this, the market is the location where sellers and buyers interact to carry out buying and selling transactions. In everyday life, implicatures are used not because one does not want to cooperate in a conversation, but there are more prioritized reasons that cannot comply with all the maxims studied in pragmatics. Sumani Market was chosen as the research site, which is located in the X Koto Singkarak District, Solok Regency. Sumani Market is one of the largest traditional markets in Koto Singkarak and serves as a major trading center. The type and research method used in this study are qualitative research with a descriptive method. The number of data points obtained on June 18, 2023, is 3 data points, on June 19, 2023, is 0 data points, on June 20, 2023, is 2 data points, on June 21, 2023, is 0 data points, on June 22, 2023, is 2 data points, on June 23, 2023, is 1 data point, on June 24, 2023, is 1 data point, on June 25, 2023, is 4 data points, from June 26 to June 30, 2023, is 0 data points, on July 1, 2023, is 3 data points, on July 2, 2023, is 5 data points, on July 3, 2023, is 0 data points, on July 4, 2023, is 1 data point, on July 5, 2023, is 0 data points, on July 6, 2023, is 1 data point, on July 7, 2023, is 1 data point, on July 8, 2023, is 0 data points, and on July 9, 2023, is 3 data points.